Oxygen Saturation Reference Value by Percutaneous Pulse Oximetry in Asymptomatic Newborn Babies in Nigeria: A Cross-Sectional Study - Obumneme Ezeanosike; Tagbo Oguonu; Ngozi Ibeziako; Bede Ibe (MDPI AG, 2016)
About 1/4 of all neonatal deaths in Nigeria are caused by birth asphyxia. Normal values of oxygen saturation vary according to regional altitudes. They are important for the screening of cyanotic congenital heart diseases and during newborn resuscitation. There is a dearth of such information in Nigeria. We determined reference values for oxygen saturation by pulse oximetry (SpO2) in asymptomatic newborns aged ≤7 days in Enugu at an altitude of 180 m. The study was cross-sectional. Neonates weighing ≥1500 g at birth were enrolled consecutively. Pre-and post-ductal oxygen saturation was measured using a Datex-Ohmeda Tuffsat® pulse oximeter with neonatal probes. Five hundred and fourteen babies comprising of 24 (4.4%) preterm and 490 (95.3%) term neonates were studied. The mean pre-ductal SpO2 of all babies was 96.1% ± 1.4% and higher than mean post-ductal SpO2 of 95.9% ± 1.4% (p = 0.022). The mean pre-ductal SpO2 were 96.1% ± 1.5% and 96.1% ± 1.3%, (p = 1.000) for males and females, respectively. The mean pre-ductal SpO2 values were higher than the mean post-ductal SpO2 for the corresponding post-natal ages.